2009
DOI: 10.1016/j.ejcnurse.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Six-Minute Walk Test: Its Implication as a Self-Administered Assessment Tool

Abstract: Adapting the 6MWT as a patient-reported outcome measure may enhance the capacity, not only for clinicians to monitor functional status, but also promote self-management by enabling individuals to monitor changes in their functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 48 publications
2
97
0
4
Order By: Relevance
“…Walking is, of course, one of the normal activities of life; it reflects the capacity to undertake daily activities. 31,32 Compared with the incremental cardiopulmonary exercise test, the 6MWT did not provide more specific information; however, its simplicity, ease of administration, low cost and routine use would advise this test evaluation in healthy subjects or patients, and in adults or children. The six-min walking test has been validated by high correlation with workloads, HR, oxygen saturation and the dyspnea responses when compared with standard bicycle ergometry and treadmill exercise tests.…”
Section: Discussionmentioning
confidence: 99%
“…Walking is, of course, one of the normal activities of life; it reflects the capacity to undertake daily activities. 31,32 Compared with the incremental cardiopulmonary exercise test, the 6MWT did not provide more specific information; however, its simplicity, ease of administration, low cost and routine use would advise this test evaluation in healthy subjects or patients, and in adults or children. The six-min walking test has been validated by high correlation with workloads, HR, oxygen saturation and the dyspnea responses when compared with standard bicycle ergometry and treadmill exercise tests.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment has frequently been used in patients with chronic disease, such as heart failure, chronic obstructive pulmonary disease, and peripheral arterial occlusive disease. [53][54][55] Patients are instructed to walk down a 100-foot corridor at their own pace, attempting to walk as much distance as possible in 6 minutes. At the end of the 6-minute interval, the total distance walked is determined and the symptoms experienced by the patient recorded.…”
Section: Exercise Protocolsmentioning
confidence: 99%
“…The six minutes walk test (6MWT) is a simple, safe and low cost test 6 that has gained important attention in the clinical and scientific fields 7,8 . The 6MWT has already been used in previous studies of patients with FM and has shown to have good reliability 5,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The 6MWT has good applicability, because it evaluates, in a global way, the integration of responses of all physiological systems involved in the performance of the exercise 10 . The distance walked during the 6MWT has been suggested to reflect the ability to performed activities of daily living (ADL) because, in general, ADL are performed at submaximal levels 6,10 . The test is also indicated for the evaluation of cardiorespiratory aptitude 10 as previous studies have reported correlations between the distance walked and oxygen consumption (r=0.51 to 0.90) 11 .…”
Section: Introductionmentioning
confidence: 99%